Confiabilidade metrológica no contexto da garantia da qualidade industrial: diagnóstico e sistematização de procedimentos - Soares Júnior, Luiz (1999)
The requirements for the reliability of measurement results and the formality of measurement procedures have increased significantly since the establishment of ISO 9000 certification. It is well known that many Brazilian companies approach metrology in an inappropriate way. The root of this problem could be understood as a lack of metrological culture in ours industries. Also, it’s weak in the academic areas the culture to show the industry the role of the metrology as a key for quality. In addition, the ISO 9000 family of standards does not contribute to clarify the metrological subject by itself, i.e., requirements for the ISO 9000 implementation are set without any kind of explanation or justification. To explore the gap between metrology practices in the Brazilian industry and the standardization in industry, two blocks of information have been compared. Standards, procedures and technical papers have been analyzed to define the state of the art regarding the application of the metrology in quality assurance. A survey has been conducted in fifteen companies certified with the ISO 9000 to define the level of application of metrological knowledge. The result of the above study shows, in many cases, the absence of a methodology for implementation of metrological systems and the lack of adequate knowledge of metrology to establish metrological procedures. Solutions are proposed to narrow the gap between the actual and the desired states of metrological reliability in the Brazilian industry. Whenever it is possible, the solutions are based on formal documents issued by the ISO. In order to simplify their application in actual industrial situations, a methodology for the implementation of metrological quality assurance has been proposed. Its feasibility has been tested by means of a real case study. This methodology provides the basis for a “Guide to Metrological Reliability”, designed to support metrology management in ISO 9000-certified companies. The basic structure of such Guide is presented in this dissertation as a hypertext, which can be used to diffuse the concept among the whole Brazilian territory using the Internet.